Ursodeoxycholyl iysophosphatidylethanolamide negatively regulates TLR-mediated lipopolysaccharide response in human THP-1-derived macrophages - Horvatova, Alzbeta; Otto, Ann-Christin; Zhang, Yuling; Gan-Schreier, Hongying; Pathil-Warth, Anita; Stremmel, Wolfgang; Chamulitrat, Walee (European journal of pharmacology, 2018)
The bile acid-phospholipid conjugate ursodeoxycholyl oleoyl-lysophophatidylethanolamide (UDCA-18:1LPE) is an anti-inflammatory and anti-fibrotic agent as previously shown in cultured hepatocytes and hepatic stellate cells as well as in in vivo models of liver injury. We hypothesize that UDCA-18:1LPE may directly inhibit the activation of immune cells. We found that UDCA-18:1LPE was capable of inhibiting the migration of phorbol ester-differentiated human THP-1 cells. We examined anti-inflammatory activity of UDCA-18:1LPE during activation of THP1-derived macrophages. Treatment of these macrophages by bacterial lipopolysaccharide (LPS) for 24h induced the release of pro-inflammatory cytokines TNF-α, IL-6 and IL-1β. This release was markedly inhibited by pretreatment with UDCA-18:1LPE by ~ 65-90%. Derivatives with a different fatty-acid chain in LPE moiety also exhibited anti-inflammatory property. Western blotting and indirect immunofluorescence analyses revealed that UDCA-18:1LPE attenuated the expression of phosphorylated p38, MKK4/MKK7, JNK1/2, and c-Jun as well as nuclear translocation of NF-κB by ~ 22-86%. After LPS stimulation, the Toll-like receptor adaptor proteins, myeloid differentiation factor 88 and TNF receptor associated factor 6, were recruited into lipid rafts and UDCA-18:1LPE inhibited this recruitment by 22% and 58%, respectively. Moreover, LPS treatment caused a decrease of the known cytoprotective lysophosphatidylcholine species containing polyunsaturated fatty acids by 43%, and UDCA-18:1LPE co-treatment reversed this decrease. In conclusion, UDCA-18:1LPE and derivatives inhibited LPS inflammatory response by interfering with Toll-like receptor signaling in lipid rafts leading to an inhibition of MAPK and NF-κB activation. These conjugates may represent a class of lead compounds for development of anti-inflammatory drugs.
Gesehen am 12.09.2019